Exploring the antecedents affecting attitude, satisfaction and loyalty on Korean cosmetic brands - HOSSEINI, Mehri Sadat (KDI School, 2015)
This study provides useful insights into international female customer purchasing behavior towards cosmetic industry in Seoul, South Korea. This study explored the elements of Country-of-Origin (COO), cultural interest, perception of brand image, perception of fashion, perception of product quality, perception of price and perception of advertising on overall attitude as well as the effect of overall attitude on satisfaction and the effect of satisfaction on loyalty. Questionnaire was the main tool of the current research which was distributed and collected randomly from 214 international female customers. The statistical methods used in this research were factor and regression analyses. The findings showed that the effects of antecedents of cultural interest, perception of brand image, perception of fashion, perception of product quality and perception of advertising on overall attitude were significant. Also, the effect of overall attitude on satisfaction and the effects of satisfaction on loyalty were significant.
Thesis(Master) --KDI School:Master of Public Policy,2015